2001
DOI: 10.1099/00207713-51-2-339
|View full text |Cite
|
Sign up to set email alerts
|

Rickettsia felis: molecular characterization of a new member of the spotted fever group.

Abstract: In this report, placement of Rickettsia felis in the spotted fever group (SFG) rather than the typhus group (TG) of Rickettsia is proposed. The organism, which was first observed in cat fleas (Ctenocephalides felis) by electron microscopy, has not yet been reported to have been cultivated reproducibly, thereby limiting the standard rickettsial typing by serological means. To overcome this challenge, several genes were selected as targets to be utilized for the classification of R. felis. DNA from cat fleas nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
95
2
5

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(112 citation statements)
references
References 41 publications
10
95
2
5
Order By: Relevance
“…We suggested that discrepancies with previously reported phenotypic findings may have resulted from contamination of R. felis cultures, which was reported after experiments by the group that provided the first description of R. felis [120]. The ELB agent was definitely characterized as a unique spotted fever group rickettsia, and finally the name R. felis was validated [19,76].…”
Section: Flea-borne Spotted Fevercontrasting
confidence: 44%
“…We suggested that discrepancies with previously reported phenotypic findings may have resulted from contamination of R. felis cultures, which was reported after experiments by the group that provided the first description of R. felis [120]. The ELB agent was definitely characterized as a unique spotted fever group rickettsia, and finally the name R. felis was validated [19,76].…”
Section: Flea-borne Spotted Fevercontrasting
confidence: 44%
“…felis is an emerging pathogen that was first isolated in a commercial colony of cat fleas (1). Upon isolation, R. felis was designated a new species (22) and on the basis of molecular data was placed in the SFG rather than the TG (9). R. felis is transmitted by fleas horizontally and vertically (4).…”
Section: Discussionmentioning
confidence: 99%
“…Spotted fever group Rickettsia are typically associated with ticks; however, there is increasing molecular evidence of one species, Rickettsia felis, in fleas including Ctenocephalides canis (Parola et al, 2003), Pulex irritans (Azad et al, 1997), Anomiopsyllus nudata (Stevenson et al, 2005). Although the list of arthropods infected with R. felis continues to grow, C. felis remains the primary arthropod host (Adams et al, 1990;Bouyer et al, 2001;La Scola et al, 2002;Pornwiroon et al, 2006). While R. felis is maintained in an opossum-flea cycle (Azad et al, 1997;Boostrom et al, 2002), there is also growing evidence that domestic cats also play a role in the maintenance cycle of R. felis (Wedincamp and Foil, 2000;Case et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Both the original account (Adams et al, 1990) and subsequent descriptions of R. felis (Higgins et al, 1996;Bouyer et al, 2001;La Scola et al, 2002;Pornwiroon et al, 2006) utilized colonized fleas infected with R. felis. Likewise, colonized cat fleas are useful for the analysis of transmission events of R. felis among flea populations (Wedincamp and Foil, 2000.…”
Section: Introductionmentioning
confidence: 99%